The Role Of Islamic Education In Promoting Peace And Tolerance : A Bibliometric Perspective - Ahmad Mujahidin; Benny Prasetiya; Febry Suprapto; Khoiriyah Khoiriyah (Immortalis Journal of Interdisciplinary Studies, 2026)
Islamic education plays a crucial role in fostering peace, tolerance, and global social harmony. In response to growing issues of intolerance and extremism, this study aims to analyze the landscape of research on the role of Islamic education in promoting peace and tolerance through a bibliometric approach. Using data from Scopus and Web of Science from 2019–2024, this research applies PRISMA 2020 protocol and utilizes VOSviewer and Bibliometrix software to identify trends, influential authors, collaboration networks, and conceptual structures within the field. The study found a significant increase in publications after 2015, with Indonesia and Malaysia emerging as leading contributors. Thematic mapping revealed four dominant clusters: religion–Islam–education, cultural anthropology–history, human–students, and engineering education–Islamic values. The findings highlight the integration of spirituality, humanism, and science as a new epistemic paradigm known as Critical Islamic Pedagogy. This paradigm bridges Islamic epistemology (ta’dib) and critical pedagogy (conscientization), positioning Islamic education as both a spiritual and social transformation tool. The novelty of this study lies in its quantitative bibliometric mapping that visualizes the global scientific network in Islamic education and peace studies, offering a data-driven foundation for future research directions. Practically, the findings contribute to developing inclusive Islamic curricula, strengthening interfaith collaboration, and enhancing Indonesia’s academic diplomacy in Islamic peace education.